Measured radio wave behavior of a partially open drain in urban environment - Lim, Soo Yong *; Pu, Chuan Chin *; Liew, Yi Hong * (2012)
This paper attempts to analyze the propagation characteristics of radio signal inside a partially open drain environment using an empirical approach. The proposed research topic concerns a unique situation in several Asian countries because the drainage systems in these countries differ notably from those in the US and Europe in that the former are partially open on the top while the latter are primarily below ground and covered. Measurement results are reported for one drain located on Sunway University campus at 2.4 and 5.8 GHz. The differences between the measurement results at the aforementioned two frequencies are discussed. These measurement results serve as a useful indicator as to how signal might behave differently in partially enclosed spaces, such as those where partially open drains exist, especially in an urban environment.